A Systematic Approach to Analyse the Sequelae of LCPD. Issue 9 (December 2013) - Tannast, Moritz; MacIntyre, Neil; Steppacher, Simon D.; Hosalkar, Harish S.; Ganz, Reinhold; Siebenrock, Klaus A.
The analysis and treatment of hips with healed Legg-Calvé-Perthes disease (LCPD) differs substantially from the treatment in the acute phase of the disease. More specifically, the treating orthopaedic surgeon is often faced with a complex three-dimensional pathomorphology of the hip that is difficult to understand and correct. To date, none of the current classification systems provide a useful decision-making algorithm with regards to the type of surgical intervention necessary to improve hip function in patients with sequelae of LCPD. The conceptual recognition of the femoroacetabular impingement (FAI) and the ability to safely dislocate the hip have revolutionised our diagnostic and therapeutic algorithm for joint-preserving surgery of hips with structural residuals of LCPD. We present a systematic approach to analyse femoral and acetabular pathomorphologic features. The resulting pathomechanisms and the surgical treatment options are presented.